Statistical Analysis of the Dissemination of Cultural Heritage in Traditional and Social Media in Burundi - Nsavyimana, Remy (European Scientific Journal, ESJ, 2025)
The objective of this paper is to determine the place of cultural heritage in newspapers, radio, television broadcasts and online media. Metadata from the Conseil National de la Communication (CNC) and Annuaire du Secteur de la Communication et des Médias (ASCM 2019) were analyzed. These traditional and online radio, as well as television stations, were selected based on their responsibility as state institutions. Thus, 13 radio stations, including 2 public and 11 private dealing with 11,397 subjects in the spoken news, are the subject of the research. A total of 354 radio programs were analyzed. In the online media, 765 articles were posted. The findings show that cultural information is relegated to second place in radio and television news and online media. Only 53 cultural items out of 765, i.e., a rate of 0.6%, are relayed online. Jimbere Magazine took the lead with 39 cultural items out of the 53 broadcasts on the 13 radio stations, at a rate of 73.5%. The political and educational sectors attracted more attention to the public and private media, respectively with 160 and 116 items, a rate of 20% and 15%. Overall, out of 11,397 subjects covered in the news on 13 radio stations broadcasting in Burundi, 11 items related to cultural heritage were broadcast, accounting for 0.43%. This has also been observed with television news at 0.5%, while no television programs related to culture were broadcast on three TV channels, namely RTNB, REMA, and MASHARIKI.